Improving the Quality of Tilapia Fish Seeds (Oreochromis Niloticus) with Selection Methods in Mina Ayu Group of Tabanan Regency Bali Province - S.A.M.P. Suryani; Faihana Ching Abdulah; Norfazreena Mohd Faudzi; D.N. Sadguna; I Wayan Arya; D.G.Semara Edi; G.A Surya Pratama (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2022)
Tilapia fish is much in demand because it has several advantages such as its distinctive taste that makes tilapia delicious after being processed in any way. Tilapia has the potential to be used as an export commodity in the form of fish fillets and the price is relatively cheap. The climate situation and the extent of freshwater fishing land are contributing factors in the development of tilapia cultivation in Indonesia. One of the efforts to increase efficiency and productivity in cultivation is fish spawning activities. Spawning activities are important for producing seeds or larvae. Female fish are 300 to 400 g and for males, 400 to 500 g, aged 5 months. Tilapia can colonize weighing 250 g and age 4 to 6 months, meaning the parent used in this study has been following the required. The maintained parent is a healthy, unformed, and complete morphological parent (SNI 01-61412009). The purpose of this study is to improve the quality of Tilapia fish seeds produced by the Mina Ayu Group of Tabanan Regency of Bali Province by a selective breeding method. Male and female tilapia broods are kept separately in hapa measuring 5x5x1m. In shelters, for the acceleration of gonad maturation before the fish are stocked in the spawning pond. The feeding given during maintenance is 2 to 3%. Individual selection methods can improve the quality and survival rate of tilapia fish larvae. The absolute length increased 1.5 cm and weight increased 0.950 mg/day with a survival rate of 80% to 90%.